Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.1117/1.jbo.17.7.075004
|View full text |Cite
|
Sign up to set email alerts
|

Optically micropatterned culture of adherent cells

Abstract: We used a liquid-crystal spatial light modulator to project 473 nm light patterns surrounding a region of adherent cells and achieved an arbitrarily micropatterned cell culture. For a group of ∼60 cells, the cell boundaries fit the pattern of light within 15% deviation of the side length. We also demonstrated a wound-healing experiment with a definite starting temporal point by using this technique. While observing mitochondrial structures in the illuminated cells, we found that the 473 nm light damaged the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…The setup used in the present work is the same as that we described in our previous publications [7,8]. In brief, the light source was a 473 nm diode-pumped solid state laser.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The setup used in the present work is the same as that we described in our previous publications [7,8]. In brief, the light source was a 473 nm diode-pumped solid state laser.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, spatial light modulators (SLMs) have been employed to facilitate a variety of cellular guidance. For example, 473 nm blue light patterns generated by a SLM had been used to conduct patterned cell proliferation [7] and guided migration [8] of adherent cells. Apparently, optical illumination is an effective way to control cell migration.…”
Section: Introductionmentioning
confidence: 99%
“…Optical contrast is a direct way of measuring a combined set of biological parameters, including tissue composition (absorption, scattering). Michelson contrast is often used in optical imaging and vision science [21][22][23] along with other several metrics, such as a simple contrast ratio (ratio dark to light) and clinically relevant Weber contrast. 24 Michelson contrast is a method of choice for quantitative contrast evaluation when the contrast of grids and other patterns need to be assessed.…”
Section: Validation Of the Approach: Contrast Measurements With Blankmentioning
confidence: 99%
“…It is also simple to couple the laser light into microfluidic devices for precise cell manipulation [4,5]. In our previous study, we had shown that the optical patterns projected on the bottom of a culture dish could enforce micropatterned culture of adherent cells [6]. On the bases of these studies, we believe that guiding cell migration by optical patterns is feasible.…”
Section: Introductionmentioning
confidence: 99%